2013
DOI: 10.1093/humrep/des467
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of calcium-signalling pathways mediating human sperm hyperactivation

Abstract: STUDY QUESTIONWhat is the prevalence of defects in the Ca2+-signalling pathways mediating hyperactivation (calcium influx and store mobilization) among donors and sub-fertile patients and are they functionally significant, i.e. related to fertilization success at IVF?SUMMARY ANSWERThis study identifies, for the first time, the prevalence of Ca2+ store defects in sperm from research donors, IVF and ICSI patients. It highlights the biological role and importance of Ca2+ signalling (Ca2+ store mobilization) for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
110
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(125 citation statements)
references
References 65 publications
9
110
0
2
Order By: Relevance
“…The fact that these substances can both activate ion channels raises the possibility that the channel underlying I Tail may contribute to the control of motility. Moreover, progesterone, which had no effect upon the sustained outward K + current but did augment I Tail , induces hyperactivation in a proportion of human sperm (Uhler et al , 1993; Fabbri et al , 1998; Teves et al , 2006; Sagare-Patil et al , 2012; Alasmari et al , 2013a, b). This response to progesterone may be critical for progress through the female tract and successful interaction with the egg and it is therefore interesting that spermatozoa from men with clinically identified fertility defects show that impaired activation by progesterone and 4-AP correlate well with reduced fertilization capacity (Alasmari et al , 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that these substances can both activate ion channels raises the possibility that the channel underlying I Tail may contribute to the control of motility. Moreover, progesterone, which had no effect upon the sustained outward K + current but did augment I Tail , induces hyperactivation in a proportion of human sperm (Uhler et al , 1993; Fabbri et al , 1998; Teves et al , 2006; Sagare-Patil et al , 2012; Alasmari et al , 2013a, b). This response to progesterone may be critical for progress through the female tract and successful interaction with the egg and it is therefore interesting that spermatozoa from men with clinically identified fertility defects show that impaired activation by progesterone and 4-AP correlate well with reduced fertilization capacity (Alasmari et al , 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…Calcium signalling and calcium store mobilisation have recently been shown to be important in Assisted Reproductive Technologies (ART) success, as responses are clearly different when patients are compared with sperm donors (Alasmari et al 2013). However, what role sperm mitochondria have in this process is open to question, although sperm mitochondria are known to uptake calcium, and have been hinted as a possible intracellular calcium store in human sperm (Costello et al 2009).…”
Section: C Signallingmentioning
confidence: 99%
“…An elevation in intracellular pH is the prerequisite for sperm hyperactivation. showed that extracellular application of cell permeant NH4Cl evokes elevation of intracellular pH, which stimulates Ca 2+ influx and induces sperm hyperactivation in bovine , but NH4Cl has negligible effect on human sperm hyperactivation (Alasmari et al, 2013).…”
Section: Functional Significance Of Catsper Channelsmentioning
confidence: 99%
“…In response to progesterone, CatSper mediates Ca 2+ influx, which is followed by Ca 2+ induced Ca 2+ release (CICR) that faclilitates the mobilization of Ca 2+ store at the sperm neck. The release of stored calcium is likely to be responsible for potent hyperactivation of human sperm perhaps by increased incidences of [Ca 2+ ]i oscillations (Alasmari et al, 2013). Moreover, what is the mechanism of Ca 2+ oscillations (repetitive transient [Ca 2+ ]i waves) during tail-tohead [Ca 2+ ]i propagation and what is the functional significance of unidirectional Ca 2+ propagation are further questions to be addressed?…”
Section: Future Questions and Perspectivementioning
confidence: 99%